Akibat Hukum Bagi Notaris yang Tidak Memungut Honorarium pada Para Pihak - Satria Kusuma, Anak Agung Ngurah Putra; Bagiastra, I Nyoman (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 7 No 01 (2022), 2022)
The purpose of this study is to determine the honorarium arrangements in the UUJN and the Notary Code of Ethics and to examine the legal consequences of notaries who do not collect honorarium to the parties. This normative law researcher examines the issue of norms, that is, there is ambiguity of norms in UUJN and KEN, that is, notaries must provide services for free to those who cannot afford it, while they should not collect honorarium below the minimum limit of association rules. This study contains legal sources, namely; primary, secondary and tertiary law materials. The results of the research found that the regulations on honorarium that apply to notaries are Article 36 UUJN related to the maximum amount of honorarium received by Notaries and Article 37 UUJN related to notaries must provide legal services free of charge, but on the other hand notaries can be sanctioned if they do not meet the rules. in Article 4 number 10 of KEN related to the minimum limit of honorarium that has been set by the association, Violations related to the honorarium of making a deed result in the Notary being sanctioned by the Notary Code of Conduct.